Answers

The Brainliest Answer!
2015-04-02T20:20:41+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Y₁ = A sin wt
y₂ = A cos wt

After superposition, the wave is given by
y = y₁ + y₂
⇒ y = A sin wt + A cos wt
⇒ y = A [ sin wt + cos wt]
⇒ y = A [ sin wt + sin (90-wt)]
⇒ y = A [ 2 × sin(wt+90-wt)/2 × cos (wt-90+wt)/2]
⇒ y = A [ 2 × sin 45 × cos (wt-45)]
⇒ y = A [ 2/√2 × cos (90-wt)]
⇒ y = √2 A cos(90-wt)
y = √2 A sin wt
1 5 1